Macroeconomic factors and firms cross-border merger and acquisitions - Amin Nordin, Bany Ariffin; Yahya, Mohamad Hisham; McGowan, Carl B. (Springer, 2016)
This study investigates the impact of macroeconomic variables on the wealth effects of cross-border acquisitions by Malaysian multinational companies. The sample consists of 159 cross-border acquisitions by Malaysian MNCs bidding in 22 countries around the world from 2000 to 2007. The macroeconomic variables examined in this study are foreign economic condition, GNP correlation between countries, and level of economic development of target country. The findings indicate that, foreign economic condition affects the wealth effect negatively, while the level of economic development of target country affects the wealth effect positively. Aside from the macroeconomic variables, we also find that English or non-English language, government’s rules index and the telecommunication infrastructure all play certain roles in the Malaysian crossborder acquisitions. Implied from this study is that, value creation of the Malaysian cross-border acquisitions is a function of the foreign economic condition and the level of economic development of the target foreign country.